The trend towards non-pharmacological psychological treatment among psychiatric patients and non-psychiatric patients. - Samia ARAR; Naila MOSANAD; Adel TOUHAMI (Social Sciences Journal, 1970)
The current study aims at exploring the attitude of mental patients and healthypeople to wards psychotherapy according to the variables of gender, mentaldisease,age ,educational level and marital status.For thispurpose, the attitude scale for pstchotherapy has been appliedon a sampleconsisting of 190 individuals, 77 ofthemare healthyand 113 havea mental disease, all ofthem visit frequently the psychiatry service at HMC.The practioners in this clicnicde signed this tool and appliedit on the study sample.The following results have been drawn from this studyمجلة العلوم الاجتماعیة العدد 14 سبتمبر2015 113:1/ 56.3% ofthe individualsin the sample showed a neutral attitude topsychotherapy, 36.3%showeda positive attitude to psychotherapy, andonly7.4% of theindividuals showed a negative attitude.2/There are differences statistically significant in the psychotherapy attitudeamong the mental patients and the healthy peoplein favour ofthe healthyones.3/There are differences statistically significant in the psychotherapy attitudeamong females and males in favour of females.4/There are no differences statistically significant in the psychotherapy attitudedue to the variables of age, education level ,and marital status.